Microbiological assessment reveals that Salmonella, Shigella and Campylobacter infections are widespread in HIV infected and uninfected patients with diarrhea in Mozambique. - Delfina Fernandes Hlashwayo; Emília Virgínia Noormahomed; Leonilde Bahule; Constance Benson; Robert T Schooley; Betuel Sigaúque; Kim E Barrett; Custódio Gabriel Bila (PLOS Global Public Health)
Diarrhea is an important cause of hospitalizations in Mozambique. However, little attention has been paid to the impact HIV infection on the prevalence or clinical manifestations of enteric bacterial infections. This study aimed to determine the prevalence of Salmonella spp., Shigella spp. and Campylobacter spp. in HIV-infected and HIV-uninfected patients with diarrhea, identify risk factors for infection, and explore the association between HIV status, viral load, and bacterial prevalence. We conducted a case-control study at the Centro de Saúde de Mavalane and Centro de Saúde 1° de Maio in Maputo, Mozambique, from November 2021 to May 2022. We recruited 300 patients, including 150 HIV-infected (cases) and 150 HIV-uninfected patients (controls), aged between 0-88 years, presenting with diarrhea. Stool samples were collected for bacterial isolation through culture, and for each HIV-infected patient, 4 ml of venous blood were obtained for viral load detection through PCR. A total of 129 patients (43.0%) had at least one bacterial infection. The prevalence of Salmonella spp., Shigella spp. and Campylobacter spp. was 33.0% (n = 99), 15.0% (n = 45) and 4.3% (n = 13), respectively. The prevalence of any bacterial infection did not differ significantly between HIV-infected (45.3%, n = 68) and HIV-uninfected patients (40.7%, = 61) (p = 0.414). Overall, having 2-3 symptoms of enteric disease (p = 0.008) and a basic education (p = 0.030) were factors associated with bacterial infection. Of the 148 patients for whom HIV-1 RNA levels were available, 115 had copy numbers ≤ 75. Another 13 had levels between 76 and 1,000 and the remaining 20 had an average of 327,218.45 copies/ml. Bivariate logistic regression found that Shigella spp. were associated with HIV (p = 0.038), although no association was found in the multivariate analysis. Enteric infections are common in both HIV-infected and -uninfected patients. Low schooling influences the occurrence of enteric infections, which highlights the need to raise awareness about their prevention.